Electrospinning preparation of Pd@Co3O4-ZnO composite nanofibers and their highly enhanced VOC sensing properties. (January 2019) - Sun, Yongjiao; Wang, Zepeng; Wang, Wenda; Li, Gang; Li, Pengwei; Lian, Kun; Zhang, Wendong; Zhuiykov, Serge; Hu, Jie; Chen, Lin
Graphical abstract: The obtained Pd@Co3 O4 -ZnO composite nanofibers gas sensors exhibit excellent gas sensing performance for VOCs. Highlights: Pure ZnO, Co3 O4 -ZnO, Pd@ZnO and Pd@Co3 O4 -ZnO nanofibers were prepared by electrospinning method. Pd@Co3 O4 -ZnO nanofibers-based gas sensors showed excellent sensing performance for VOCs detection, especially towards ethanol. The enhanced gas sensing performance of Pd@Co3 O4 -ZnO nanofibers could be attributed to sensitization of Pd and the p-n junction between Co3 O4 and ZnO. Abstract: In this paper, pure ZnO, Co3 O4 -ZnO, Pd@ZnO and Pd@Co3 O4 -ZnO composite nanofibers were synthesized by electrospinning method. Multiple characterizations were employed to investigate the crystal structure, composition, morphology, and bonding states of the Pd@Co3 O4 -ZnO composite nanofibers. The sensing properties of the as-synthesized nanofibers were evaluated toward different volatile organic components (VOCs) including ethanol, acetone, isopropanol and formaldehyde under the various operating temperatures. The obtained results have clearly demonstrated that the Pd@Co3 O4 -ZnO composite nanofibers exhibits significantly enhanced VOC sensing performance compared with other nanofibers. Specifically, the response of Pd@Co3 O4 -ZnO composite nanofibers toward 200 ppm ethanol is 59 at 240℃, which is much higher than that of ZnO nanofibers. The enhanced VOC sensing properties of Pd@Co3 O4 -ZnO composite nanofibers could be attributed to the electronic and chemical sensitizations of Pd and the p-n junction formation at the interface of Co3 O4 and ZnO.